Pelaksanaan Asimilasi dalam Pembinaan Anak Negara di Lembaga Pemasyarakatan Karangasem - I Made Satya Adhi Wicaksana; I Made Minggu Widyantara; I Pt Gd Seputra (Jurnal Preferensi Hukum, 2020)
Assimilation embodies the correctional principle which requires that prisoners not be separated from society. This assimilation was given in order to provide guidance for prisoners, provide skills or education for prisoners to prepare themselves to live independently in the community after being free to undergo criminal justice. Assimilation can allow providing opportunities for prisoners to be able to socialize with the community through coaching, as well as activities carried out with the community. So that later when it is free to be able to return to the midst of society as part of the community and that is not less important, it can provide provision of education and skills that can be used in the community later. The formulation of the problem in this study is: how is the implementation of assimilation as an effort to foster State Children in the Karangasem Correctional Institution and what obstacles are faced in implementing assimilation in the Karangasem Penitentiary. The type of research used in this study is empirical legal research. The results of the discussion in this study are as follows: Implementation of assimilation in the Karangasem Penitentiary based on the Decree of the Minister of Justice of the Republic of Indonesia Number M.01. PK.04-10 of 1999, and for prisoners related to drug cases, especially users, the coaching is carried out strictly, making it difficult to give assimilation efforts. The obstacles faced in the implementation of assimilation in the Karangasem Penitentiary include: the lack of officers of Karangasem prison institutions who have professional and professional education, lack of interest in serving people in Karangasem Prison, lack of implementing officers for prisoner training, experts are still less like psychiatrists, psychologists, sociologists, doctors and others according to the operational technical needs of Karangasem state detention centers.